PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KRYAWAN PT. TELKOM INDONESIA WILAYAH SEMARANG - Isfandi, Dimas Nur; Lubis, Nawazirul; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2015)
The development today’s business world requires organizations to constanly open to the changing business environment by taking into account the quality of human resources to improve employee performance. Factors can be used to improve the performance of the employee one of them is good leadership and the ideal and condusive work environment. PT. Telkom Indonesia is currenly undergoing a transformation that changes the organization’s leadership structure into decentralization and doing development, both infrastructure and human development. However, the change is not in accordance with the company’s expectation because there are employees with low performance.The purpose of this research was to determine the effect of leadership and work environment on the performance employees of PT. Telkom Indonesia Semarang. This type of research is explanatory research, with data collection through interviews and observation. The sampling technique used purposive sampling with a sample of 74 respondents employees of PT. Telkom Indonesia Semarang. Testing techniques to determine the accuracy and reliability of the item questionnaire as a research  instrument using validity and reliability test. Analysis technique using cross tabulation, correlation coefficient, simple and multiple regression analysis, coefficient of determination, and a significance test ( t test and F test).             Results and discussion of this research show that in partial leadership has a positive impact on employee performance supported by contributions from the coefficient of determination 6,4%. While the work environment has a greater positive impact on employee performance supported by contributions from the coefficient of determination  16%.            Based on the result of the research it is suggested, the leadership to set a good example in the work, routine maintenance and equipment room should also be made to support employees in their work, as well as the necessary training leadership with experiental learning (seminars, study the competition games, contemplation) to develop creativity.